Using a social media campaign to promote public health awareness among pharmacy students - Angie Leon-Salas; María S Quesada-Morua (Facultad de Farmacia, Universidad de Granada, 2020)
ABSTRACT Introduction: To describe pharmacy students' perceptions about an innovative teaching activity planned to introduce the concept of public health and its relationship with pharmacy. Method: Elements of Public Health' students had to take at least one picture illustrating how public health impacts their communities or place of residence. To do so, they received a Spanish This is Public Health campaign sign that had to be used to create a post in their personal Facebook profiles. At the end of this activity, students completed a brief survey evaluating their perceptions. Results: The This is Public Health campaign allowed students to comprehend public health concepts and recognized its relationship with pharmacy. Moreover, using this didactic strategy increased their interest and motivation towards public health-related topics. Students were able to identify the use of social media as a good way of presenting health information to their contacts. Conclusions: It is possible to motivate pharmacy students to know more about their role in public health activities using innovative teaching strategies. Public health educators need to integrate these strategies with classic classroom lessons and activities, accordingly to the changing learning needs of students that are growing up within a more technological background.